Mengatasi Hambatan Literasi Digital: Strategi Pemasaran Digital bagi Pelaku UMKM Desa Truko - Agusta Praba Ristadi Pinem; Prind Triajeng Pungkasanti; Gita Aprinta (Universitas Muhammadiyah Semarang, 2024)
The development of information technology that is not accompanied by the acceleration of digital literacy, especially in the MSME sector, can result in failure to compete in an era of high use of digital marketing. This service activity aims to increase understanding and use of digital marketing among MSMEs in Truko Village, Kendal Regency. Through training and mentoring activities using the Participatory Action Research (PAR) method, MSMEs are actively involved in the digital marketing learning process. The results of the situation analysis show that although the majority of MSMEs have basic knowledge about digital marketing, implementation is still limited. Training activities are focused on digitalizing products and promotions, using tools such as photoroom, single landing page, Linktree, and WA Business. Evaluation of the results shows a significant increase in the use of digital marketing tools, reaching an 80% increase in the use of Linktree. This article summarizes the process, results and positive impact of community service activities in improving the skills and business competitiveness of Truko Village MSMEs in the digital era.